Keeping up the spirit. Internal communication in an increasingly virtual work environment - Julia Stranzl; Daniel Wolfgruber; Sabine Einwiller; Jana Brockhaus (Academic Society for Management & Communication, 2021)
Alongside the transformation of work environments during the COVID-19 pandemic, internal communication underwent a decisive switch towards more virtuality. Although a change was long overdue, its speed created a multitude of challenges through the reduced personal contact. Therefore, a research team at the University of Vienna has addressed the following questions: What are the challenges for internal communication in an increasingly virtual work environment? How to achieve the goals of internal communication virtually? What are the dangers of an increasingly virtual work environment? How can internal communication support to avoid them? – – Durch die Virtualisierung und die Covid-19-Pandemie wird auch die interne Kommunikationsarbeit zunehmend digitaler. Neben den Vorteilen, die die virtuelle Zusammenarbeit mit sich bringt, zeigen sich auch einige Herausforderungen. So lassen sich mit weniger persönlichem Kontakt zum Beispiel Mitarbeitende schwieriger einbinden und motivieren. Ein Forschungsteam der Universität Wien hat sich deswegen mit folgenden Fragen beschäftigt: Welchen Herausforderungen begegnen interne Kommunikationsexpertinnen und Kommunikationsexperten in einer zunehmend virtuellen Arbeitswelt? Wie können die Ziele der internen Kommunikation in einem virtuellen Kontext erreicht werden? Was sind mögliche negative Auswirkungen in einer zunehmend virtuellen Arbeitswelt? Was kann getan werden, um negative Effekte zu vermeiden?
Keywords: 650